2006
DOI: 10.1186/1465-9921-7-135
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 mRNA in sputum of asthmatic patients: linking T cell driven inflammation and granulocytic influx?

Abstract: Background: The role of Th2 cells (producing interleukin (IL-)4, IL-5 and IL-13) in allergic asthma is well-defined. A distinct proinflammatory T cell lineage has recently been identified, called Th 17 cells, producing IL-17A, a cytokine that induces CXCL8 (IL-8) and recruits neutrophils. Neutrophilic infiltration in the airways is prominent in severe asthma exacerbations and may contribute to airway gland hypersecretion, bronchial hyper-reactivity and airway wall remodelling in asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
391
2
8

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 517 publications
(439 citation statements)
references
References 41 publications
27
391
2
8
Order By: Relevance
“…This is the first demonstration that a T H 2 cytokine can coordinate with a proinflammatory cytokine, such as IL-17A, to potentiate a T H 2 response. 11,18,[28][29][30][31] This discovery emphasizes the uniqueness of epithelia-derived IL-19 in allergic diseases and suggests important roles for IL-13 and IL-17A in IL-19 regulation. [32][33][34] We hypothesize that airway epithelial IL-19 is induced by IL-17A and T H 2 cytokines, mainly IL-13, to further potentiate a T H 2-dominant response in a positive feedback manner in the context of allergic airway diseases, such as asthma.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This is the first demonstration that a T H 2 cytokine can coordinate with a proinflammatory cytokine, such as IL-17A, to potentiate a T H 2 response. 11,18,[28][29][30][31] This discovery emphasizes the uniqueness of epithelia-derived IL-19 in allergic diseases and suggests important roles for IL-13 and IL-17A in IL-19 regulation. [32][33][34] We hypothesize that airway epithelial IL-19 is induced by IL-17A and T H 2 cytokines, mainly IL-13, to further potentiate a T H 2-dominant response in a positive feedback manner in the context of allergic airway diseases, such as asthma.…”
Section: Discussionmentioning
confidence: 98%
“…[32][33][34][35][36] IL-17A also plays a role in human asthmatic patients and in airways of allergic animals. 18,28,30,[37][38][39] Studies have found that in patients with moderate-to-severe asthma, neutrophils are found to be more abundant than eosinophils in the bronchoalveolar lavage fluid. 30,31,40 IL-17A can promote neutrophil recruitment, which might contribute to certain asthmatic phenotypes characterized by both high neutrophil counts and IL-17A expression.…”
Section: Discussionmentioning
confidence: 99%
“…A true correlation between IL-17A and neutrophils was demonstrated by BULLENS et al [38] when assessing mRNA for IL-17A in sputum cells from patients with mild and moderate-to-severe asthma. However, the increase in this mRNA was modest compared with healthy control subjects but the results did not suggest that the transcription of IL-17A is sensitive to treatment with inhaled glucocorticoids.…”
Section: Sputum Samplesmentioning
confidence: 99%
“…Thus IL-17A expression in sputum or bronchial mucosal biopsies has been correlated with bronchial hyperresponsiveness (16), Nanzer et al 5 granulocyte infiltration (17) and production of fibrogenic mediators by bronchial fibroblasts (18).…”
Section: Introductionmentioning
confidence: 99%